The silver cow : a Welsh tale - Cooper, Susan, 1935- (Atheneum, 1983)
A young Welsh boy is rewarded for his beautiful harp playing with a silver cow, the gift of the magic people living in the lake. The cow makes his family rich but when his father becomes greedy the magic people take their revenge.